Potensi Wisata Ekonomi Syariah Berbasis Kearifan Lokal (Studi Kasus Kabupaten Tanggamus) - Devy Septi Heryani (Dinar Islamic Review, 2021)
This research is field research. The required data is taken through interview and documentation techniques which are then analyzed by qualitative descriptive analysis to describe the conditions/phenomena that occur in the field during the research and will carry out a cause and effect analysis. The results showed that not all visitors can enter the tourism in Kiluan Bay because local people still adhere to the local culture on the island and limited access to the location. Tourists who visit still have to dress modestly as determined by the manager.